Pengaruh GCG, Company Size, Company Age, Profitabilitas Terhadap Pnegungkapan Sustainability Report - Renisha; Amelia Setiawan; Hamfri Djajadikerta (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2024)
The study aims to examine the effect of the number of members of the board of commissioners and the board of directors, gender of the audit committee, company size, company age, and profitability on the completeness of sustainability report disclosure in several companies in the Fast-Moving Consumer Goods (FMCG) industry in Indonesia. In a business era that increasingly emphasizes the principles of sustainability and transparency, sustainability reports are an important indicator that reflects the company's commitment to responsible business practices. However, the level of completeness of sustainability report disclosure between companies still varies greatly. This study uses a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method through SmartPLS software. Data were obtained from sustainability reports and annual reports of 15 companies in the FMCG industry listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The results showed that most of the independent variables, such as the number of commissioners, gender of the audit committee, and profitability have a significant effect on the completeness of sustainability report disclosure. These findings are expected to contribute to the development of good corporate governance practices, as well as encourage the improvement of the quality and transparency of sustainability reporting in the FMCG industry. Penelitian bertujuan untuk menguji pengaruh jumlah anggota dewan komisaris dan dewan direksi, gender komite audit, company size, company age, dan profitabilitas terhadap kelengkapan pengungkapan sustainability report pada beberapa perusahaan dalam industri Fast-Moving Consumer Goods (FMCG) di Indonesia. Dalam era bisnis yang semakin menekankan prinsip keberlanjutan dan transparansi, sustainability report menjadi salah satu indikator penting yang mencerminkan komitmen perusahaan terhadap praktik bisnis yang bertanggung jawab. Namun, tingkat kelengkapan pengungkapan sustainability report antar perusahaan masih sangat bervariasi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode Partial Least Squares-Structural Equation Modeling (PLS-SEM) melalui perangkat lunak SmartPLS. Data diperoleh dari sustainability report dan annual report 15 perusahaan di industri FMCG yang terdaftar di Bursa Efek Indonesia (BEI) selama periode 2021-2023. Hasil penelitian menunjukkan bahwa sebagian besar variabel independen, seperti jumlah dewan komisaris, gender komite audit, dan profitabilitas berpengaruh signifikan terhadap kelengkapan pengungkapan sustainability report. Temuan ini diharapkan dapat memberikan konstribusi dalam pengembangan praktik tata kelola perusahaan yang baik (good corporate governance), serta mendorong peningkatan kualitas dan transparansi pelaporan keberlanjutan di industri FMCG.